First examples of functionalisation of meso-aryl tetrabenzotriazaporphyrins (TBTAPs) through cross-coupling reactions. Issue 39 (30th September 2015) - Alharbi, Nuha; Tizzard, Graham J.; Coles, Simon J.; Cook, Michael J.; Cammidge, Andrew N.
Abstract: Recent synthetic advances have given convenient access to tetrabenzotriazaporphyrins (TBTAPs) functionalised with meso -aryl substituents. In this paper we report the first examples of further functionalization of the meso -sites through Suzuki–Miyaura and copper-free Sonagashira cross-coupling reactions of the meso- (bromophenyl)TBTAPs, demonstrating the breadth of new materials design now possible in the hybrid macrocycles. Graphical abstract: